O impacto do uso de agrotóxicos nos arrozais do Município de Cachoeira do Arari: a expansão territorial do uso dos agrotóxicos no Município de Cachoeira do Arari e as consequências para o meio ambiente e a saúde pública - RODRIGUES, Mosineide dos Santos (2024)
This article analyzes the management of pesticides in the State of Pará, focusing on the quantity of registered products and companies, and the implications for human health and the environment. The research reveals that there are currently a total of 1,842 registered pesticide products and 131 operating companies in the region. Based on the analysis of literature and available data, the study highlights that prolonged exposure to these products can have serious health repercussions, including acute and chronic conditions, as well as negatively impact the environment. The article also discusses the importance of strict regulations, periodic reassessments, and safe agricultural practices to mitigate the risks associated with pesticide use. It concludes that an integrated approach, involving regulation, monitoring, and farmer education, is essential to ensure safety and sustainability in pesticide use, promoting a healthier and more sustainable environment.